Efficacy of Xinbao pill on chronic heart failure: Study protocol of a multicenter, randomized, double-blind, placebo-controlled trial - Wang, Yuanping; Li, Jiahua; Yan, Jiaqi; Wang, Yulin; Cheng, Yuanyuan; Liu, Zhongqiu; Wang, Dawei (Frontiers in Pharmacology, 2022)
Abstract Introduction: Chronic heart failure (CHF) is a common cardiovascular disease. In China, Xinbao pill (XBP) is widely used as an adjuvant therapy for CHF. However, there is still a lack of high-quality clinical evidence. We designed this multicenter, randomized, double-blind, placebo-controlled trial to critically evaluate the efficacy and safety of XBP as an adjuvant treatment for patients with CHF. Methods and analysis: We will recruit 284 patients with a clinical diagnosis of “heart-kidney yang deficiency syndrome” CHF receiving treatment in 6 hospitals in China. Patients will be randomly assigned, in a 1:1 ratio, to the treatment or control group using a central randomization system. All patients will receive conventional drug therapy for heart failure combined XBP (Guangdong Xinbao Pharmaceutical Co., Ltd, Guangdong, China) or a placebo. Study physicians, subjects, outcome assessors, and statisticians will be blinded to the group assignment. The primary outcome will be the change in the proportion of patients who show a decrease in serum NT-proBNP of more than 30% after treatment. Secondary outcomes are NYHA class, 6-minute walk distance test, Minnesota Quality of Life Scale score, endpoint events, serum NT-proBNP, echocardiographic parameters, and traditional Chinese medicine (TCM)symptom score. Adverse events will be monitored throughout the trial. Data will be analyzed according to a predetermined statistical analysis plan. Discussion: The results of this study will provide solid evidence of the safety and efficacy of XBP as an alternative and complementary treatment measure for patients with CHF. Ethics and dissemination: This trial was approved by the ethics committee at Shunde Hospital of Guangzhou University of Chinese Medicine (KY-2020117). We will publish the study results. Trial registration number: Chinese Clinical Trial Registration Center (ChiCTR2000038492).